2017
DOI: 10.1016/j.lungcan.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of implementing computed tomography screening for lung cancer in Taiwan

Abstract: Low-dose CT screening for lung cancer among high-risk smokers would be cost-effective in Taiwan. As only about 5% of our women are smokers, future research is necessary to identify the high-risk groups among non-smokers and increase the coverage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 32 publications
4
49
0
Order By: Relevance
“…Most of those interventions were minimally invasive ENBguided and EBUS-guided bronchoscopy procedures. Although we did not conduct a formal costeffectiveness analysis, our results support prior publications from Europe [32], the United Kingdom [33], Asia [34], and the United States [35,36] demonstrating the cost-effectiveness of screening and incidental nodule programs.…”
Section: Discussionsupporting
confidence: 76%
“…Most of those interventions were minimally invasive ENBguided and EBUS-guided bronchoscopy procedures. Although we did not conduct a formal costeffectiveness analysis, our results support prior publications from Europe [32], the United Kingdom [33], Asia [34], and the United States [35,36] demonstrating the cost-effectiveness of screening and incidental nodule programs.…”
Section: Discussionsupporting
confidence: 76%
“…In Taiwan, the majority of lung cancer cases identified by the use of lowdose CTscreening were adenocarcinoma at early stage. us, implementation of CT screening in Taiwan would be more cost-effective than in the Western countries where adenocarcinoma is less prevalent [35,36]. Radiation exposure and risk of malignancy arising from the use of low-dose CT screening for lung cancer might be a major concern, but many screening trials showed that these related risks can be considered acceptable and even negligible considering the associated substantial mortality reduction [37].…”
Section: Discussionmentioning
confidence: 99%
“…Each matched patient underwent follow-ups from the initiation of EGFR-TKI until September 2018 to verify the survival status. By using a semiparametric method explained in detail in our previous article [13], we extrapolated the survival to lifetime to estimate the life expectancy of patients receiving one of three first-line treatments. The extrapolation method has been shown to be effective via computer simulations [14], mathematical proof [15] and corroboration by examples of lung cancer cohorts [13,16,17].…”
Section: Effectivenessmentioning
confidence: 99%